Selective hydrodeoxygenation of BHET using bimetallic Pt–Sn/γ-Al2O3 catalysts: Catalyst design, reaction pathway, and performance evaluation - Hidayat, Syarif; Han, Jeonghun; Kim, Jinsoo; Hwang, Hyun Tae; Zhou, Xinxing; Choi, Jong In; Zhang, Haoxing; Hong, Do-Young; Ha, Jeong-Myeong; Kim, Seung-Soo (Elsevier BV, 2025)
In this research, bis(2-hydroxyethyl) terephthalate (BHET), an essential monomer obtained from the glycolysis of PET, served as a model compound for hydrodeoxygenation (HDO) over bimetallic Pt-Sn/γ-Al2O3 catalysts within a fixed-bed reactor at atmospheric pressure. A series of catalysts with varying Pt/Sn ratios (Pt7Sn3, Pt7.5Sn2.5, Pt8Sn2, and Pt8.5Sn1.5) were prepared via incipient wetness impregnation method and extensively characterized using XRD, BET, H2-TPR, NH₃-TPD, SEM-EDX, and XPS. Among the formulations, Pt7.5Sn2.5 exhibited optimal performance, achieving complete BHET conversion (100 %) and a deoxygenation degree of 94 % at 400 °C, with high selectivity toward benzene (40.56 %), toluene (7.59 %), and ethylbenzene (45.42 %). This superior activity is attributed to the synergistic interaction between Pt and Sn, which promotes efficient Csingle bondO bond cleavage while minimizing over‑hydrogenation and cracking. Temperature studies revealed 400 °C to be the most favorable temperature for hydrocarbon selectivity and minimal gas-phase carbon loss, while 5 h time on stream testing confirmed catalyst with minimal coke formation. Reaction pathway analysis showed that BHET deoxygenation proceeded via benzoic acid and benzaldehyde intermediates. This study highlights the potential of Ptsingle bondSn catalysts to enable the mild and efficient deoxygenation of PET-derived compounds, promoting the sustainable upcycling of polyester waste. The proposed strategy provides a scalable and practical route for the chemical recycling of PET, contributing to a circular economy in plastic waste management.